A new species of Ochterus Latreille (Hemiptera Ochteridae) from the Philippines - Gapud, V.P. (Philippines Rushing Water Publishers, 1995)
"Ochiterus surigaoensis Gapud, a new species from Surigao del Sur, is described and its salient features illustrated."
Keywords: Surigao del Sur, Philippines; Ochteridae; Hemiptera